Shared Genetic Etiology of Primary Dilated Cardiomyopathy and Ischemic Dilated Cardiomyopathy - Sun, Yang; Xiao, Lei; Li, Ke; Wang, Hong; Song, Xiuli; Li, Zongzhe; Li, Chenze; Chen, Yanghui; Li, Shiyang; Huang, Jin; Tan, Lun; Hu, Dong; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Mutations in genes encoding sarcomere and cytoskeletal proteins are major causes of primary dilated cardiomyopathy (DCM). Likewise, ischemic myocardial injury is a major cause of secondary cardiac remodeling, which, in a subset, is severe and resembles DCM. The latter is referred to as ischemic dilated cardiomyopathy (IDCM). We postulated the presence of pathogenic and likely pathogenic variants (PVs and LPVs, respectively) in genes known to cause primary DCM might predispose the heart to severe cardiac dilatation and dysfunction post myocardial ischemic injury, i.e., IDCM. Methods: We performed whole-exome sequencing in 1,041 patients with primary DCM, 215 patients with IDCM, and 414 healthy controls. Indices of cardiac size and function were similar between those with primary and ischemic DCM. PVs and LPVs, including the truncating variants in 36 genes known to cause primary DCM were identified and compared among the three groups. Results: Pathogenic variants and LPVs were detected in 266 individuals, comprised of 215/1,041 (20.7%) patients with DCM, 27/215 (12.6%) patients with IDCM, and 24/414 (5.8%) control individuals. PVs and LPVs in the TTN gene were the most common and detected in 130/1,041 (12.5%) of patients with DCM, 15/215 (7.0%) of cases with IDCM, and 10/414 (2.4%) control individuals. Of 135 TTNtv, 118 involved exons that were >90% spliced in. These variants were found in 120/1,041 (11.5%) of DCM patients, 6/215 (2.8%) of IDCM cases, and only in 1/414 (0.2%) of the control population (p < 0.001 among the three groups). Conclusions: Pathogenic variants and LPVs in genes known to cause primary DCM are enriched in patients with IDCM, suggesting that such variants function as susceptibility alleles for cardiac dilatation and dysfunction in post myocardial ischemic injury. Thus, IDCM shares a partial genetic etiology with the primary DCM.